Retrotransposition creates sloping shores: a graded influence of hypomethylated CpG islands on flanking CpG sites - Grandi, Fiorella C.; Rosser, James M.; Newkirk, Simon J.; Yin, Jun; Jiang, Xiaoling; Xing, Zhuo; Whitmore, Leanne; Bashir, Sanum; Ivics, Zoltán; Izsvák, Zsuzsanna; Ye, Ping; Yu, Y. Eugene; et al. (Genome Research, 2015)
Long interspersed elements (LINEs), through both self-mobilization and trans-mobilization of short interspersed elements and processed pseudogenes, have made an indelible impact on the structure and function of the human genome. One consequence is the creation of new CpG islands (CGIs). In fact, more than half of all CGIs in the genome are associated with repetitive DNA, three-quarters of which are derived from retrotransposons. However, little is known about the epigenetic impact of newly inserted CGIs. We utilized a transgenic LINE-1 mouse model and tracked DNA methylation dynamics of individual germline insertions during mouse development. The retrotransposed GFP marker sequence, a strong CGI, is hypomethylated in male germ cells but hypermethylated in somatic tissues, regardless of genomic location. The GFP marker is similarly methylated when delivered into the genome via the Sleeping Beauty DNA transposon, suggesting that the observed methylation pattern may be independent of the mode of insertion. Comparative analyses between insertion- and non-insertion-containing alleles further reveal a graded influence of the retrotransposed CGI on flanking CpG sites, a phenomenon that we described as “sloping shores.” Computational analyses of human and mouse methylomic data at single-base resolution confirm that sloping shores are universal for hypomethylated CGIs in sperm and somatic tissues. Additionally, the slope of a hypomethylated CGI can be affected by closely positioned CGI neighbors. Finally, by tracing sloping shore dynamics through embryonic and germ cell reprogramming, we found evidence of bookmarking, a mechanism that likely determines which CGIs will be eventually hyper- or hypomethylated.